2020
DOI: 10.1017/mor.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Director Networks, Political Connections, and Earnings Quality in Malaysia

Abstract: This article investigates the relationship between director networks and earnings quality in Malaysia. Using data on 4,416 individual directors who served on the boards of 745 firms listed on Bursa, Malaysia during 2011, we map the entire network of directors and generate measures to reflect the size and quality of information within the network. We find a negative and significant relationship between the overall connectedness of a director's network and the firm's earnings quality. In addition, we find a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 97 publications
(203 reference statements)
4
10
0
Order By: Relevance
“…Therefore, in China, boards with higher centrality are more likely to use their network directly or indirectly to connect with political authority, intervening in news reports, social media and other public opinion systems, thereby weakening the exposure risks of symbolic management. Similar logic has also been found in other corporate practices; for example, firms with higher board centrality implement more inefficient mergers and acquisitions ( Tao et al, 2019 ) and higher earnings management ( Abdul Wahab et al, 2020 ), because they are more likely to circumvent the influence of public opinion supervision. Second, boards with higher centrality help to reduce information asymmetry among them and their connecting firm, making it easier for their firms to obtain and utilize information ( Larcker et al, 2013 ), namely, allowing them to effectively observe and learn the successful experience of symbolic practices from other peers and then use them in their own firms ( Nandy et al, 2020 ).…”
Section: Theoretical Background and Hypothesessupporting
confidence: 59%
“…Therefore, in China, boards with higher centrality are more likely to use their network directly or indirectly to connect with political authority, intervening in news reports, social media and other public opinion systems, thereby weakening the exposure risks of symbolic management. Similar logic has also been found in other corporate practices; for example, firms with higher board centrality implement more inefficient mergers and acquisitions ( Tao et al, 2019 ) and higher earnings management ( Abdul Wahab et al, 2020 ), because they are more likely to circumvent the influence of public opinion supervision. Second, boards with higher centrality help to reduce information asymmetry among them and their connecting firm, making it easier for their firms to obtain and utilize information ( Larcker et al, 2013 ), namely, allowing them to effectively observe and learn the successful experience of symbolic practices from other peers and then use them in their own firms ( Nandy et al, 2020 ).…”
Section: Theoretical Background and Hypothesessupporting
confidence: 59%
“…Another important recent stream has examined financial reporting quality, considering earnings quality (Abdul-Wahab et al , 2020; Chaney et al , 2011; Kang and Zhang, 2018; Shin et al , 2018), corporate social responsibility disclosure (Muttakin et al , 2018), environmental information disclosure (Cheng et al , 2017), related party transactions (Habib et al , 2017) and fraudulent financial reporting (Wang et al , 2017); however, we found limited evidence for associations between PCON firms and analysts' earnings forecasts. In China, He and Ma (2019) discovered that political connections in Chinese state-owned enterprises encouraged analysts to be optimistic, thus generating misleading recommendations.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 64%
“…These ties might be through network connections or state ownership [51,52]. One form of this phenomenon is to have government officials in the service of an organization's executive or directors, literally embedding political affiliates in economic organizations [53,54]. This phenomenon is on the horns of a dilemma as on one hand, it may leverage the firms with ingress to government's valuable resources but on the other hand, it makes them liable for extra limelight of government monitoring.…”
Section: Political Ties and Quality Of Corporate Social Responsibility Disclosurementioning
confidence: 99%